A New Structure for Sen Transformer Using Three Winding Linear Transformer - Chia Lailypour; Murteza Farsadi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
In this paper a new structure for "Sen" transformer is introduced, by using three winding transformers with neutral point in order to use negative value of compensating voltage. Combination of taps will be adjusted by a novel algorithm, to control the required active and reactive powers, separately. This paper tries to focus on three parts. First of all there is an introduction on the concept of ST structure what comes next is a try to work on power flow control by using PI controllers and an algorithm to find the best and efficient combination of taps, finally proposed idea and algorithm will be implement on a practical system. Implementation of the system consist of two separated and related parts. The first one is about transmission line and Sen Transformer and the interaction between them. The second part is programing codes that adjust taps for required active and reactive powers.